2021
DOI: 10.1111/vsu.13619
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of scar revision after inadequate primary excision of cutaneous mast cell tumors in 85 dogs (2000–2013)

Abstract: Objective: To determine the frequency of residual tumor, and factors associated with local recurrence and disease progression in dogs with incompletely excised mast cell tumors (MCT) following scar revision surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 29 publications
(120 reference statements)
0
11
0
Order By: Relevance
“…Regardless of the technique used, it is necessary to avoid excessive manipulation of the lesion, seeking to avoid stimulation of mast cell degranulation and its consequent adverse effects [ 159 ]. In cases of tumor recurrence after initial excision, the main associated factor tends to be histological grading, with low recurrence rates after excision of grade 1 or II MCTs [ 160 , 161 ].…”
Section: Therapeutic Approachmentioning
confidence: 99%
“…Regardless of the technique used, it is necessary to avoid excessive manipulation of the lesion, seeking to avoid stimulation of mast cell degranulation and its consequent adverse effects [ 159 ]. In cases of tumor recurrence after initial excision, the main associated factor tends to be histological grading, with low recurrence rates after excision of grade 1 or II MCTs [ 160 , 161 ].…”
Section: Therapeutic Approachmentioning
confidence: 99%
“…It is consistently reported that complete surgical resection is the treatment of choice for mast cell tumors, and complete histologic margins may be considered curative for lowgrade tumors [1,22,38,[41][42][43][44]47,50,51,53,54,[59][60][61]64,65,[70][71][72][73][74]83,[87][88][89][90][91][92][93][94][95][96][97][98]. Mast cell tumors can be deemed non-resectable or not amenable to curative-intent surgical margins.…”
Section: Discussionmentioning
confidence: 99%
“…The prognosis and subsequent management of the patient after definitive local therapy is dichotomized by the MCT grade. Typically, low-grade tumors require no further treatment, even if incompletely excised, and patients are expected to have good to excellent outcomes, while patients with high-grade tumors are expected to succumb to their disease and require intensive multi-modal therapeutic strategies [1,2,6,[35][36][37][38][39]48,[52][53][54][59][60][61][62][63][64][65][66][67]. This then raises the question of how preoperative glucocorticoid treatment may impact the histological parameters and criteria for grade determination and the immunohistochemical detection of proliferation indices in canine MCTs.…”
Section: Introductionmentioning
confidence: 99%
“…It is consistently reported that complete surgical resection is the treatment of choice for mast cell tumors, and complete histologic margins may be considered curative for low-grade tumors [1,22,[41][42][43][44]47,50,51,55,60,62,63,66,67,[71][72][73][74][75]84,86,[89][90][91][92][93][94][95][96][97][98][99][100][101][102]. Mast cell tumors can be deemed non-resectable or not amenable to curative-intent surgical margins.…”
Section: Discussionmentioning
confidence: 99%
“…The prognosis and subsequent management of the patient after definitive local therapy is dichotomized by MCT grade. Typically, low-grade tumors require no further treatment, even if incompletely-excised, and patients are expected to have good to excellent outcomes; while patients with high-grade tumors are expected to succumb to their disease and require intensive multi-modal therapeutic strategies [1,2,6,[35][36][37][38][39]48,52,55,[60][61][62][63][64][65][66][67][68][69]. This then raises the question of how pre-operative glucocorticoid treatment may impact histological parameters, criteria for grade determination and immunohistochemical detection of proliferation indices in canine MCTs.…”
Section: Introductionmentioning
confidence: 99%